Multi-objective optimal design of TMDs for increasing critical flutter wind speed of bridges - Hai-Le Bui (Elsevier, 2022)
Tuned mass dampers (TMDs) to improve long-span bridges' critical flutter wind speed have been widely investigated. However, the optimization of the parameters of TMDs to increase the aerodynamic stability of the long-span bridge girders in the most efficient way has not been properly considered. The present study shows a novel approach in optimizing the parameters of TMDs installed in the sectional model of the long-span bridge to maximize the critical flutter wind speed of the system based on a multi-objective optimization method. The objective functions, maximizing critical flutter wind speed and minimizing TMDs’ mass, are included simultaneously. The configuration parameters of TMDs are considered as design variables. Balancing composite motion optimization (BCMO), a recently published meta-heuristic optimization algorithm, is utilized as the optimization tool in this research. The present study can be considered as the primary research in multi-objective optimization of the bridge-TMDs systems. The simulation results indicate that when installing optimized TMDs, the critical flutter wind speed of the system is significantly increased. The proposed approach can be extended to design long-span bridges optimally with other devices.